2019
DOI: 10.1007/s10800-019-01372-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on discharge behavior and performance of As- and B-doped silicon anodes in non-aqueous Si–air batteries under pulsed discharge operation

Abstract: Very high theoretical specific energies and abundant resource availability have emerged interest in primary Si-air batteries during the last decade. When operated with highly doped Si anodes and EMIm(HF) 2.3 F ionic liquid electrolyte, specific energies up to 1660 Wh kg Si −1 can be realized. Owing to their high-discharge voltage, the most investigated anode materials are ⟨100⟩ oriented highly As-doped Si wafers. As there is substantial OCV corrosion for these anodes, the most favorable mode of operation is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In lieu of recent publications, primarily on active Si anode dissolution and its implementation in primary nonrechargeable cells entailing harsh alkaline aqueous solutions or concentrated fluoride-based electrolytes, [16][17][18][19] we devised a novel procedure focused on mild surface activation aimed at mitigating parasitic corrosion, previously found to be detrimental to long term storage. [19][20][21][22][23][24][25][26] The electrolytes were comprised of varied concentrations of fluoridebased organic salts in designated aprotic solvents. Beforehand, the solvents were tested in a Karl Fischer coulometric titrator and found to contain less than 20 ppm of H 2 O. Fluoro-hydrogenate ionic liquids, used as the sole source of fluoride, were incompatible with the KF titrator, and therefore were dried in an anhydrous CaF 2 stir reactor, filtered, and tested for residual calcium contamination via ICP test (<1 ppm).…”
Section: Silicon Surface Activationmentioning
confidence: 99%
See 4 more Smart Citations
“…In lieu of recent publications, primarily on active Si anode dissolution and its implementation in primary nonrechargeable cells entailing harsh alkaline aqueous solutions or concentrated fluoride-based electrolytes, [16][17][18][19] we devised a novel procedure focused on mild surface activation aimed at mitigating parasitic corrosion, previously found to be detrimental to long term storage. [19][20][21][22][23][24][25][26] The electrolytes were comprised of varied concentrations of fluoridebased organic salts in designated aprotic solvents. Beforehand, the solvents were tested in a Karl Fischer coulometric titrator and found to contain less than 20 ppm of H 2 O. Fluoro-hydrogenate ionic liquids, used as the sole source of fluoride, were incompatible with the KF titrator, and therefore were dried in an anhydrous CaF 2 stir reactor, filtered, and tested for residual calcium contamination via ICP test (<1 ppm).…”
Section: Silicon Surface Activationmentioning
confidence: 99%
“…[ 16,17 ] In the past decade, several publications reported the incorporation of active Si anodes in primary air‐battery designs, with 1.2 V nominal working voltage. [ 17–26 ] The anodic electrochemical dissolution of highly doped n‐type silicon in EMI∙(HF) 2.3 F ionic liquid (initiated at a potential of ‐1.4 V vs Fc/Fc + ) was ascribed to the following suggested reaction, forming dissolvable SiF 4 gas in the ionic liquid: [ 16,26 ] Sibadbreak+12false(HFfalse)2FSiF4goodbreak+8false(HFfalse)3Fgoodbreak+4e normalEgoodbreak=1.4normalV vs Fc/Fc+\[ \begin{array}{*{20}{c}}{{\rm{Si}} + 12{{({\rm{HF}})}_2}{{\rm{F}}^ - } \to {\rm{Si}}{{\rm{F}}_4} + 8{{({\rm{HF}})}_3}{{\rm{F}}^ - } + 4{e^ - }\;\;{\rm{E}} = - 1.4{\rm{V}}\;{\rm{vs}}\;{\rm{Fc/F}}{{\rm{c}}^ + }}\end{array} \] Coulombic efficiency, lack of in‐depth understanding regarding the related cell mechanism, ambiguity on the kinetics and products formation in the Si–air cells, precluded addressing the potential rechargeability of cells based on Si as an active anode. Recently, several research groups reported successful Si electrodeposition also in ionic liquids (RTILs), [ 28–49 ] providing further insight into the Si redox mechanism and kinetics in various electrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations